2015
DOI: 10.1007/s10464-014-9696-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Prevention of Childhood Anxiety: Engaging Parents in an Underserved Community

Abstract: Selective prevention programs hold the promise of alleviating child anxiety symptoms, decreasing the risk for emotional problems across the lifespan. Such programs have particular public health import for young children of poor, underserved communities. Identifying factors related to parent engagement, and methods to improve engagement, are paramount in the effort to develop anxiety-focused, community prevention programs. This feasibility study investigated the effect of an enhanced recruitment strategy to max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…Although the inclusion criteria allowed for a broader range of study designs, only experimental trials met the additional inclusion criteria (i.e., studies assessing parent engagement). The included studies can be categorised into two not-mutually-exclusive groups: (1) studies measuring predictors of engagement ( n = 17; Baker, Arnold & Meagher, 2011 ; Brody et al, 2006 ; Byrnes et al, 2012 ; Calam et al, 2008 ; Carpentier et al, 2007 ; Eisner & Meidert, 2011 ; Fleming et al, 2015 ; Garvey et al, 2006 ; Heinrichs et al, 2005 ; Hellenthal, 2009 ; Mauricio et al, 2014 ; Mian, Eisenhower & Carter, 2015 ; Nordstrom, Dumas & Gitter, 2008 ; Plueck et al, 2010 ; Reedtz et al, 2011 ; Skärstrand et al, 2009 ; Winslow et al, 2009 ), and (2) studies that evaluated engagement methodologies ( n = 9; Aalborg et al, 2012 ; Bjørknes, Jakobsen & Nærde, 2011 ; Byrnes et al, 2012 ; Calam et al, 2008 ; Carpentier et al, 2007 ; Eisner & Meidert, 2011 ; Heinrichs, 2006 ; Helfenbaum-Kun & Ortiz, 2007 ; Mian, Eisenhower & Carter, 2015 ). Some studies had dual aims (i.e., evaluation of an engagement methodology and measurement of predictors; Calam et al, 2008 ; Carpentier et al, 2007 ; Eisner & Meidert, 2011 ; Mian, Eisenhower & Carter, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the inclusion criteria allowed for a broader range of study designs, only experimental trials met the additional inclusion criteria (i.e., studies assessing parent engagement). The included studies can be categorised into two not-mutually-exclusive groups: (1) studies measuring predictors of engagement ( n = 17; Baker, Arnold & Meagher, 2011 ; Brody et al, 2006 ; Byrnes et al, 2012 ; Calam et al, 2008 ; Carpentier et al, 2007 ; Eisner & Meidert, 2011 ; Fleming et al, 2015 ; Garvey et al, 2006 ; Heinrichs et al, 2005 ; Hellenthal, 2009 ; Mauricio et al, 2014 ; Mian, Eisenhower & Carter, 2015 ; Nordstrom, Dumas & Gitter, 2008 ; Plueck et al, 2010 ; Reedtz et al, 2011 ; Skärstrand et al, 2009 ; Winslow et al, 2009 ), and (2) studies that evaluated engagement methodologies ( n = 9; Aalborg et al, 2012 ; Bjørknes, Jakobsen & Nærde, 2011 ; Byrnes et al, 2012 ; Calam et al, 2008 ; Carpentier et al, 2007 ; Eisner & Meidert, 2011 ; Heinrichs, 2006 ; Helfenbaum-Kun & Ortiz, 2007 ; Mian, Eisenhower & Carter, 2015 ). Some studies had dual aims (i.e., evaluation of an engagement methodology and measurement of predictors; Calam et al, 2008 ; Carpentier et al, 2007 ; Eisner & Meidert, 2011 ; Mian, Eisenhower & Carter, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study (reported in two articles) recruited through personal invitation to the study, either through researcher or professional networks ( Bjørknes, Jakobsen & Nærde, 2011 ; Bjørknes & Manger, 2013 ). Two studies used pre-screening measures to provide individualised feedback to parents and offered the program to those parents whose children were at increased risk for developing mental health problems ( Mian, Eisenhower & Carter, 2015 ; Plueck et al, 2010 ). Only one study ( Carpentier et al, 2007 ) explicitly used known psychological theories to guide their recruitment methods.…”
Section: Resultsmentioning
confidence: 99%
“…• Streghtening Families Program, SFP (Kumpfer & Johnson, 2007) • Programa de Competencia Familiar: Versión Española del SFP (Orte et al, 2018(Orte et al, , 2016(Orte et al, , 2014 • Strengthening Families Program: For Parents and Youth 10-14 (Aalborg et al, 2010;Byrnes et al, 2012; 2018) • Mindfulness-Enhanced Strengthening Families Program 10-14 (MSFP 10-14) (Coatsworth et al, 2018) • Family Matters (FM) (Aalborg et al, 2010;Byrnes et al, 2012) • Incredible Years (Axford et al, 2012;Baker et al, 2011) • Early Risers Conduct Problems Prevention Program (Bloomquist et al, 2012) • Behavioral Parent Training Program (Chacko et al, 2009(Chacko et al, , 2012(Chacko et al, , 2016 • Strategies to Enhance Positive Parenting [STEPP] program (Chacko et al, 2009(Chacko et al, , 2012(Chacko et al, , 2016 • Adolescent Transitions Program (ATP) eb The Family Check-Up (Connell et al, 2007) • Triple P (Eisner y Meidert, 2011;Heinrichs et al, 2005) • Preventive Parent (PT) Training (Garvey et al, 2006) • Bridges to High School Program (Mauricio et al, 2014) • Healthy Families America (HFA) (McCurdy et al, 2006) • Women, Infants and Children (WIC) (Mian et al, 2015) • eHealth Familias Unidas (Perrino et al, 2018) • Early Alliance (Prinz et al, 2001) • Families Program of the Multisite Violence Prevention Project (MVPP) (Quinn et al, 2010) • FRAME-Fatherhood Relationship And Marriage Education (Rienks et al, 2011) • Strong Families program (Ross & DeVoe, 2014) • Coping Power Program (Ryan et al, 2009) Fuente: Elaboración propia.…”
Section: Resultsmentioning
confidence: 99%
“…Otra forma de reducir el rechazo y aumentar el reclutamiento es preparar a los padres para la intervención (Morawska & Sanders, 2006), mediante llamadas de reclutamiento personalizadas, cartas individuales y recordatorios (Finan, Swierzbiolek, Priest, Warren, & Yap, 2018). No obstante, estos procedimientos parecen ser menos efectivos para facilitar la retención de participantes (Mian, Eisenhower, & Carter, 2015).…”
Section: Estrategias Para Minimizar Las Barreras a La Participaciónunclassified
“…To understand this diversity, researchers must engage participants living with vulnerable conditions (e.g., poverty, poor health, language difficulties). However, people living with vulnerable conditions are particularly challenging to engage in research (Lindenberg, Solorzano, Vilaro, & Westbrook, ; Mian, Eisenhower, & Carter, ; Schnirer & Stack‐Cutler, ) due to numerous, well‐documented participation barriers (Barratt, Levickis, Naughton, Gerner, & Gibbons, ; Brown, Marshall, Bower, Woodham, & Waheed, ; George, Duran, & Norris, ). People living with vulnerable conditions often do not have time, childcare, and transportation supports to participate in research, as well as they may experience language or literacy barriers and harbour feelings of mistrust and stigma related to research.…”
Section: Introductionmentioning
confidence: 99%